A Review on Current Practices of Plastics Waste Management and Future Prospects - Bhandari, Netra Lal; Bhattarai, Sulakshana; Bhandari, Ganesh; Subedi, Sumita; Dhakal, Kedar Nath (Journal of Institute of Science and Technology, 2021)
Inefficient solid waste management of plastics and polymeric materials is one of the global challenges leading to environmental deterioration. This challenge has brought alarming concern to minimize volume of such wastes released into the environment. The concern proposes a solution to the existing problems to some extent by reuse, recycling, and efficient conversion of waste materials into alternative application. Chemical and thermo-mechanical conversion of plastic wastes into energy and their biodegradation were taken into account. Consequently, some newly employed recycling and conversion techniques of plastic wastes, and possible future alternatives with recommendations are reviewed in this article